The global evolution, changing landscape and future of financial markets : from traditional to digital - Raza, Syed Ali; Syed, Darakhshan; Rizwan, Syed; Ahmed, Maiyra (Emerald Publishing Limited, 2025)
The financial service industry is already changing significantly as a result of four important areas of innovation; the development of artificial intelligence (AI), innovation of Blockchain (Decentralized system), the fintech revolution, and the emergence of crypto-assets. The authors examine each of these areas separately in The Global Evolution, Changing Landscape and Future of Financial Markets, assisting the reader in comprehending the context, history, and basics of these trends. While new technologies offer exciting opportunities for innovation and growth, they also present new challenges and risks that must be carefully managed. The chapters present the ways in which inclusion and diversity can lead to more effective and responsible digital financial products and services, while also confronting the barriers facing underrepresented groups in the digital finance industry. Through this book readers are provided with a comprehensive understanding of the evolving financial landscape and the importance of creating a more inclusive and diverse digital finance ecosystem.